Legal Standing Negara Pihak Konvensi Dalam Menggugat Negara Pihak Lainnya Atas Pelanggaran Konvensi Genosida 1948 - Taohi, Indisari Sahril; Anwar, Arman; Wattimena, Josina Agustina Yvonne (Faculty of Law Universitas Pattimura, 2025)
The birth of the 1948 Genocide Convention has bound all states parties to the convention and established obligations for them to prevent and punish genocide. However, in practice there are still countries that violate these obligations. The consequences of these violations can lead to disputes between fellow State Parties to the Genocide Convention, leading to a challenge at the International Court of Justice (ICJ). However, the process of suing must meet the requirements of legal standing, namely that the plaintiff has an interest or is directly affected by the action being sued. The research method used is normative juridical using a statute approach, conceptual approach and case approach. The results that the author concludes show that the International Court of Justice has provided arrangements regarding legal standing, namely only states are given access to disputes before the Court. The disputing state is also required to give consent to the jurisdiction of the International Court of Justice. The implementation of the legal standing of the State Parties to the Genocide Convention is carried out through Article 9 of the Genocide Convention which gives the convention parties the right to bring their disputes before the International Court of Justice. This right stems from the common interest of all States Parties to the Convention to ensure the prevention, eradication and punishment of genocide, by committing to fulfill the obligations contained in the convention, so that any state, not only the state affected by the violation can bring a claim against another state at the International Court of Justice to ensure compliance with the Genocide Convention.